Materials Design for N2O Capture: Separation in Gas Mixtures - Ballesteros-Plata, Daniel; Cecilia-Buenestado, Juan Antonio; Barroso-Martín, Isabel; Jiménez-Jiménez, José; Infantes-Molina, Antonia; Rodríguez-Castellón, Enrique (IOAP-MDPI, 2022)
The adsorption of greenhouse gases (GHG) as a method to reduce their emissions into the atmosphere is an alternative that is easier to implement industrially and cheaper than other existing technologies, such as chemical capture, cryogenic separation, or membrane separation. The vast majority of works found in the literature have focused their efforts on capturing CO2 as it is the largest GHG. However, although N2O emissions are not as large as CO2, the impact that N2O has on the stratosphere and climate is much larger in proportion, despite which there is not much research on N2O capture. Since both gases are usually emitted into the atmosphere together (along with other gases), it is necessary to design selective adsorbents capable of capturing and separating these gases from each other and from other gases, to mitigate the effects of climate change. This review aims to compile the existing information to date on porous adsorbents, the characteristics of the N2O adsorption processes and, above all, aims to focus the reader’s gaze on the importance of designing selective adsorbents for greenhouse gas mixtures.
Keywords: Carbón activado; N2O adsorption; N2O/CO2 selectivity; Porous materials; MOFs; Zeolites; Activated carbons